The influence of psychological ownership and social support on organizational resilience: the mediating role of organizational identity - He, Kui; Oláh, Judit; Hasan, Morshadul (Journal of Business Economics and Management, 2022)
Faced with a complex and volatile environment, improving the resilience of organizations to resist various risks, enhancing the viability of enterprises, and ultimately achieving sustainable development capabilities has become a top priority for business managers. This study first explores the relationship between employee psychological ownership, organizational resilience, and social support by combining the relevant literature, constructing a theoretical research model, and proposing hypotheses. Through statistical analysis of 332 valid questionnaires, the results show that employee psychological ownership positively impacts organizational resilience. Also, social supports positively affect organizational resilience and organizational identity in employee psychological ownership, and social supports and organizational resilience both play an intermediary role.